2013
DOI: 10.1007/s00204-013-1098-1
|View full text |Cite
|
Sign up to set email alerts
|

Human Ntera2 cells as a predictive in vitro test system for developmental neurotoxicity

Abstract: Developmental neurotoxicity (DNT) of environmental chemicals is a serious threat to human health. Current DNT testing guidelines propose investigations in rodents, which require large numbers of animals. With regard to the "3Rs" (reduction, replacement, and refinement) of animal testing, alternative testing strategies are needed in order to refine and reduce animal experiments and allow faster and less expensive screening. The goal of this study was to establish components for a human cell-based test system to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 44 publications
0
49
0
Order By: Relevance
“…In other recent studies, valproic acid inhibited mouse neurosphere formation in vitro (Zhou et al, 2011) and increased neuronal apoptosis in cells differentiating from human progenitor cells in vitro (Wang et al, 2011). Moreover, a study that used the NT2 teratocarcinoma stem cell line reported that valproic acid (in the high millimolar range) reduced differentiating cell viability and (in the micromolar range) reduced neural differentiation and migration (Stern et al, 2014). The molecular mechanisms underlying the impact of valproic acid on neural development are not well understood and may involve the regulation of several hundred genes and multiple pathways (see Hill et al, 2013) but were not the purpose of this investigation.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In other recent studies, valproic acid inhibited mouse neurosphere formation in vitro (Zhou et al, 2011) and increased neuronal apoptosis in cells differentiating from human progenitor cells in vitro (Wang et al, 2011). Moreover, a study that used the NT2 teratocarcinoma stem cell line reported that valproic acid (in the high millimolar range) reduced differentiating cell viability and (in the micromolar range) reduced neural differentiation and migration (Stern et al, 2014). The molecular mechanisms underlying the impact of valproic acid on neural development are not well understood and may involve the regulation of several hundred genes and multiple pathways (see Hill et al, 2013) but were not the purpose of this investigation.…”
Section: Discussionmentioning
confidence: 84%
“…Importantly, we used human EC stem cells because the neurons derived from them display key morphological, molecular and functional properties of mature neurons including voltage-and ligand-gated ion channels (Coyne et al, 2011;Stewart et al, 2004). Moreover, teratocarcinoma stem cells have been shown to have value in screening for developmental neurotoxicity with heavy metals such as lead, mercury and aluminum (Laurenza et al, 2013;Stern et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diverse workshops and meetings during the past 10 years have summarized the problems, the available assays and roadmaps for DNT in vitro assays and methods (Coecke et al, 2007; Lein et al, 2007; Crofton et al, 2011; Crofton et al, 2014; Bal-Price et al, 2015a; Bal-Price et al, 2015b). Several in vitro studies have been able to reproduce some of the relevant processes that occur in the brain such as neuronal differentiation (Hartley et al, 1999), migration (Stern et al, 2014), cell-cell interaction, neuritic development, synaptogenesis, myelinogenesis (Liu et al, 2012) and neurotransmission (Hogberg et al, 2011). In addition, they showed to be predictive of DNT (Hogberg et al, 2010; Hogberg et al, 2011; Laurenza et al, 2013; Pallocca et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A particular research focus is how arsenic influences signaling pathways relevant in cell stress response and carcinogenesis (Chen et al 2014;Wang et al 2014;Weng et al 2014;Liu et al 2013;Jiang et al 2013;Pastoret et al 2013). Recently, also epigenetic alterations (Gribble et al 2014), developmental toxicity (Zimmer et al 2014;Stern et al 2014) and metabolism as well as transport of arsenic Yu et al 2013;Xu et al 2013;Watanabe and Hirano 2013) have been intensively studied. The present review of GundertRemy and colleagues which comprehensively compares arsenic exposure likely to cause adverse effects in humans to current exposure levels of the general European population demonstrates that research of arsenic is of high practical relevance and should lead to regulatory action to reduce the risk of the general population.…”
mentioning
confidence: 99%